2018
DOI: 10.3390/nu10081048
|View full text |Cite
|
Sign up to set email alerts
|

Blackberry Feeding Increases Fat Oxidation and Improves Insulin Sensitivity in Overweight and Obese Males

Abstract: Berries and other anthocyanin-rich treatments have prevented weight gain and adiposity in rodent models of diet-induced obesity. Their efficacy may be explained by modulation of energy substrate utilization. However, this effect has never been translated to humans. The objective of this study was to evaluate the effects of berry intake on energy substrate use and glucoregulation in volunteers consuming a high-fat diet. Twenty-seven overweight or obese men were enrolled in a randomized, placebo-controlled cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 52 publications
1
65
1
3
Order By: Relevance
“…Twenty-seven overweight or obese men were enrolled in a randomized, placebo-controlled crossover study. Subjects were fed a high-fat diet which contained either 600 g/day blackberries or a calorie and carbohydrate matched amount of gelatin for seven days [ 38 ]. Blackberry consumption may promote increased fat oxidation and improved insulin sensitivity in overweight or obese males fed a high fat diet.…”
Section: Why Anthocyanins?mentioning
confidence: 99%
“…Twenty-seven overweight or obese men were enrolled in a randomized, placebo-controlled crossover study. Subjects were fed a high-fat diet which contained either 600 g/day blackberries or a calorie and carbohydrate matched amount of gelatin for seven days [ 38 ]. Blackberry consumption may promote increased fat oxidation and improved insulin sensitivity in overweight or obese males fed a high fat diet.…”
Section: Why Anthocyanins?mentioning
confidence: 99%
“…Diabetes complications can be exacerbated by oxidative stress. Antioxidant consumption has been reported to help prevent such complications from worsening (Solverson et al, 2018). These authors tested seventeen overweight or obese men by feeding them either 600 g of blackberries, or carbohydrate-matched gelatin of the same caloric content.…”
Section: Anti-hypoglycemic Effectsmentioning
confidence: 99%
“…These authors tested seventeen overweight or obese men by feeding them either 600 g of blackberries, or carbohydrate-matched gelatin of the same caloric content. The results showed that fat oxidation and insulin sensitivity increased for the men fed blackberries, with younger subjects demonstrating the best improvement (Solverson et al, 2018). A cross sectional study of 1,997 women investigated flavonoid consumption broken down by class against diabetesrelated markers such as fasting glucose, insulin, and C-reactive protein.…”
Section: Anti-hypoglycemic Effectsmentioning
confidence: 99%
“…Recently published study by Solverson et al. (2018) showed that overweight or obese men fed a HF diet, which included 600 g blackberries per day for 1 week, exhibited increased insulin sensitivity and fat oxidation …”
Section: Adipose Tissue Inflammation and Obesitymentioning
confidence: 99%